ANALISIS ECONOMIC VALUE ADDED (EVA) SEBAGAI ALAT UKUR KINERJA KEUANGAN BANK SYARIAH - Yuricke Marshella; Karuniawati Hasanah (UNIVERSITAS PGRI MADIUN, 2018)
This study uses descriptive studies with the aim to provide an overview of the aspects that are relevant in this case to help managers make decisions for the company. The subject of this research is a Sharia Commercial Bank registered with the Financial Services Authority. The instruments in this study are quarterly financial reports from Sharia Commercial Bank. The analysis technique used in this research is descriptive analysis.The results showed that Bank Muamalat pioneered the sharia banks in creating EVA but in 2016 and 2017 experienced a decline in economic value to not add value. This can happen because the muamalat decreases earnings to increase the amount of debt in the company. While the BJB bank does not create much added value even EVA is obtained is always negative this can be influenced by the amount of profit less than the amount of debt high enough, this can trigger kurannya interest shareholeder to invest in the bank.Keywords: Sharia Commercial Bank, Economic Value Added